The Effect of Diets Containing Jack Bean (Canavalia ensiformis L.) Fermented by Rhizopus oligosporus on the Production Performance and the Egg Quality of Quail - Utami , Sri; Rusmana, Denny; Wiradimadja, Rachmat; Rochana, Ana (International Journal of Poultry Science, 2019)
Background and Objectives: The scarcity and high prices of raw materials for poultry feed are major problems that can hinder the production of poultry. One alternative ingredient that can be used in feed is jack beans. This study was conducted to determine the effect of diets containing jack beans fermented by Rhizopus oligosporus on the production performance and the egg quality of quail. Materials and Methods: The main materials used in this research were jack bean products after fermentation by R. oligosporus and 1-month-old quail(not yet egg-laying). The study was carried out using a completely randomized design consisting of 5 diet treatments; each treatment was replicated 4 times and each replication contained 15 quail. Four kinds of diet contained fermented jack beans at 7.5, 15.0, 22.5 and 30.0% and the control diet did not contain fermented jack beans. The observed parameters included feed consumption, egg production, feed conversion, eggshell thickness, egg yolk color and egg yolk cholesterol. Results: The level of fermented jack beans in the diets of layer quail had no significant effect (p>0.05) on feed consumption and eggshell thickness. However, egg weight, daily egg production, feed conversion, egg yolk color intensity and egg yolk cholesterol were significantly affected by the jack bean treatment (p<0.05). Conclusion: The use of fermented jack beans in the feed formulations of layer quail is safe up to 22.5%. Feeds containing 22.5% fermented jack beans can increase egg weight and egg production and reduce the feed conversion ratio of quail and the cholesterol levels of quail eggs. Jack beans fermented by R. oligosporus can be used as a food ingredient in the feed formulations of layer quail to increase the quantity and quality of quail eggs.